PLANTWIDE CONTROL AND DYNAMICS BEHAVIOR OF AN INTEGRATED PLANT COUPLING NITROBENZENE HYDROGENATION AND METHYL-CYCLOHEXANE DEHYDROGENATION - JAVAID, Ahtesham; BILDEA, Costin S. (Studia Universitatis Babeș-Bolyai Chemia, 2020)
Coupling of exothermic and endothermic processes is an application of process intensification where two or more processes can be combined in single unit for better utilization of material and energy. Nitrobenzene hydrogenation and dehydrogenation of Methyl cyclohexane in a single adiabatic reactor was investigated and found efficient, stable and economical in the previous study. The scope of this research is to implement plantwide control structure to analyze the dynamics behavior of an integrated system using Aspen Dynamics. Integrated plants where un-reacted reactants are recycled have high sensitivity towards disturbances. The complexity of the plant is reduced by fixing flow rates of reactants at reactor inlet using feedback control strategy. On introduction of individual and combined disturbances in flow rates of reactants ±10%, the system showed robust behavior and achieved stable operation. The system allows production rate changes keeping high purity of products.